A Arquitectura no espaço agrícola: intervenção na Quinta da Mesquita - Ana Rita Rosa Luís (2016)
The dissertation presented here is focused on the elaboration of an intervention project of a set of buildings from the late XIX century/ early XX century. This aggregation, with housing and agricultural character, is inserted on the Quinta da Mesquita's area which is located in the Cela's Parish, Alcobaça's County. Through a very thoughtful research and work investigation as well as a building survey, the first aim is thought to be analysing its location, to restitute its history, to understand how the spaces work out and to study its architectural and constructive characteristics. Combining this analyses and interpretation process with the author's personal experience and vision, it's questioned how the farm can contribute to the local development as it was once done, trying, in a more practical way, to delineate an answer through this project which could be able to respect and recover the pre-existence, at the same time that it adapts to the new programmatic and comfort demands.